40 Impact of time from symptom onset on the diagnostic performance of high-sensitivity cardiac troponin for type 1 myocardial infarction. (6th June 2022) - Lowry, Matthew; Doudesis, Dimitrios
Abstract : Introduction: In patients with suspected acute coronary syndrome, cardiac troponin is used to identify those at high and low risk of future cardiovascular events. The ability of high-sensitivity assays to quantify low levels of cardiac troponin has led to the development of algorithms which allow the early rule-out or rule-in of myocardial infarction on the basis of a single presentation sample. The performance of a single test approach will in part be dependent on the time taken for troponin to reach a specified risk stratification threshold following injury. Guidelines recommend single test strategies are not used in early presenters. However, it is unclear how diagnostic performance changes over multiple time points and whether caution should be applied when using single test strategies in late presenters. Methods: In a secondary analysis of a multicentre trial of consecutive patients with suspected acute coronary syndrome, we evaluated the diagnostic performance of presentation high-sensitivity cardiac troponin I to rule-out or rule-in type 1 myocardial infarction across four groups based on the time from symptom onset to troponin sampling (<3 hours, 4 to 6 hours, 7 to 12 hours and ≥12 hours) using common rule-out (<2ng/L & <5ng/L) and rule-in (>99th centile, >64ng/L) thresholds. Results: In 41, 104 (mean 60 (49–74) years), 3, 692 (9%) patients had an adjudicated diagnosis of type 1 myocardial infarction. For both rule-out thresholds, sensitivity for was highest 7–12 hrs following symptom onset and lowest in patients presenting within 3 hrs. In patients presenting within 3 hrs, a rule-out threshold of <2ng/L resulted in superior sensitivity and negative predictive value compared with a threshold of 5ng/L (99.4% [95% confidence intervals 98.9–99.7%] and 99.7% [99.5- 99.9%] vs 96.7% [95.7- 97.6%] and 99.3% [99.1 to 99.5%] respectively). For the rule-in of myocardial infarction, sensitivity for the 99th centile and >64ng/L threshold was lowest in patients presenting within 3 hrs (71.7% [69.3–74.1%] vs 46.5% [44.1–49.2%] respectively), increased with time from symptom onset and was highest in those presenting >12 hrs from symptom onset (92.5% [90.5–94.5%] vs 70.0% [66.8–73.2%] respectively). Specificity and positive predictive value for both thresholds was greatest 7–12 hrs following symptoms and declined in those presenting >12 hrs after symptom onset. Conclusion: The ability of a single cardiac troponin sample to rule-in or rule-out type 1 myocardial infarction is influenced by the time from symptom onset to troponin sampling with. A limit of detection strategy may facilitate the safe rule-out of type 1 myocardial infarction in patients presenting within 3 hrs from symptom onset. Conflict of Interest: None